2019
DOI: 10.1590/0100-3984.2019.0044
|View full text |Cite
|
Sign up to set email alerts
|

The many faces of pseudomyxoma peritonei: a radiological review based on 30 cases

Abstract: Objective: To determine the most common imaging features of pseudomyxoma peritonei (PMP), as well as the histologic subtypes of the primary tumors. Materials and Methods: We reviewed 30 cases of women with pathologically confirmed PMP. Only computed tomography scans were available. All cases were retrospectively studied by four radiologists, working independently. We identified the most common imaging findings, the predominant primary site of the disease, and the growth pattern. The most common sites of recur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…A computed tomography scan can also show low-attenuation lesions or loculated ascites scattered throughout the peritoneal cavity and individual peritoneal or omental nodules (omental cake in advance disease). Often it is hard to detect the primary tumor in a CT scan [17]. Moreover, many authors have reported appendiceal tumors and PMP, which mimic ovarian masses, and the patient underwent surgery with this diagnosis, as in our case [18][19][20].…”
Section: Diagnosismentioning
confidence: 78%
See 1 more Smart Citation
“…A computed tomography scan can also show low-attenuation lesions or loculated ascites scattered throughout the peritoneal cavity and individual peritoneal or omental nodules (omental cake in advance disease). Often it is hard to detect the primary tumor in a CT scan [17]. Moreover, many authors have reported appendiceal tumors and PMP, which mimic ovarian masses, and the patient underwent surgery with this diagnosis, as in our case [18][19][20].…”
Section: Diagnosismentioning
confidence: 78%
“…Imaging modalities, mainly ultrasound and CT, may establish the diagnosis [2,5,11,17]. A specific sonography marker is the so-called "onion skin sign" and its "dumbbell structure" [18].…”
Section: Diagnosismentioning
confidence: 99%
“…The secretory function of the columnar cells was severely damaged, which led to a decrease in mucus secretion ( 2 , 6 , 18 ). Moreover, the concentrated tumor mass resulted in liver scalloping and omental cake ( 19 , 20 ). The current study results also demonstrated that the presence of omental cake predicted a higher pathological grade.…”
Section: Discussionmentioning
confidence: 99%
“… 33 It indicates that these gelatinous ascites and tumor cells follow the abdominal fluid circulation through lymphoid aggregates. 34 Mucus-secreting cells migrate with peritoneal fluid and keep in dynamic circulation because of the influence of body position, intraperitoneal pressure, and physical peritoneal fluid circulation. 35 Cells merely implant on tissues of relative standstill.…”
Section: Standard Regimen Of Pmp Treatmentmentioning
confidence: 99%